Comparison of FRAX in postmenopausal Asian women with and without type 2 diabetes mellitus: a retrospective observational study - Wang, Chen (J Int Med Res, 2019)
OBJECTIVE: To compare the fracture risk in postmenopausal Asian women with or without type 2 diabetes mellitus (T2DM). METHODS: The study cohort comprised data from consecutive postmenopausal women with T2DM that were retrieved from a prospectively maintained institutional database from 2001 to 2009. Postmenopausal women without DM from the Medical Examination Center from 2001 to 2009 formed the control cohort. The primary endpoint was the World Health Organization Fracture Risk Algorithm (FRAX, revised 2013) score. The secondary endpoint was bone mineral density (BMD). RESULTS: There were 1014 individuals included for the assessment (T2DM, n=500 and non-DM, n=514). Based on the FRAX model, the risk of major osteoporotic fractures and hip fractures over the next 10 years was higher in the T2DM group compared with the non-DM group. Compared with the T2DM group, the non-DM group had a lower BMD. After adjusting for age, gender, history of alcohol consumption, smoking status, body mass index, and low-density lipoprotein, the differences were statistically significant. CONCLUSIONS: Compared with postmenopausal women without DM, postmenopausal women with T2DM had a significantly higher fracture risk calculated using the FRAX model. Early intervention for postmenopausal women with T2DM may be necessary, although T2DM is associated with a high BMD.